The Implementation of Read, Ask, Paraphrase Technique in the News Reading Comprehension - Purba, Ezra Susanti Harnita; Octavianna, Yessy; Pakpahan, Carolina (Universitas Islam Ahmad Dahlan (UIAD), 2024)
The purpose of this study is to investigate the significance of applying the RAP technique in learning activities in reading classrooms. The researcher employed a quantitative experimental research strategy for this study. The participants in this study were students in classes IX-A and IX-B at SMP Gajah Mada Medan who were in their ninth grade. Selecting samples, researchers used the term cluster random sampling by choosing two classes. There are 60 students total; there are 15 pupils in each class. Two groups of students were formed; the experimental group and the control group. The control group was instructed in traditional ways, whereas the experimental group received therapy (the RAP approach). An exam with multiple choice questions is the tool used to gather data. To assess the data, the t-test formula was used. The data was evaluated using the t-test procedure. The analysis's findings demonstrate that, at a significance level of 0.05 and with 28 degrees of freedom (df), those served exceed the t-table (3.86> 2.44). This indicates that students' learning scores have been positively impacted by the use of the RAP technique in the teaching and learning process, particularly when it comes to the reading of news articles for class.